2019
DOI: 10.1097/meg.0000000000001349
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transjugular intrahepatic portosystemic shunt for treatment of variceal bleeding in patients with cirrhosis with or without spontaneous portosystemic shunt

Abstract: Background and aims Transjugular intrahepatic portosystemic shunt (TIPS) is an effective intervention for portal hypertensive complications in cirrhosis. Spontaneous portosystemic shunts (SPSSs) may increase the risk of post-TIPS complications and mortality. This study was done to evaluate the safety and efficacy of TIPS for treating variceal bleeding between patients with and without SPSSs. Patients and methods The clinical data of 467 consecutive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…They also showed that these patients did not have a higher risk of rebleeding, recurrence of ascites, TIPS dysfunction or death of any cause. Similar results were obtained byLeng et al in a recent study that evaluated the efficacy of TIPS combined with SPSS embolization in variceal bleeding, comparing the results and risks with patients without SPSSs 107. In this study, a control group submitted to TIPS with nonembolized SPSSs was not included.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…They also showed that these patients did not have a higher risk of rebleeding, recurrence of ascites, TIPS dysfunction or death of any cause. Similar results were obtained byLeng et al in a recent study that evaluated the efficacy of TIPS combined with SPSS embolization in variceal bleeding, comparing the results and risks with patients without SPSSs 107. In this study, a control group submitted to TIPS with nonembolized SPSSs was not included.…”
supporting
confidence: 71%
“…Some studies suggest that pre-existing large SPSSs increase the risk of post-TIPS HE, which diminishes when these shunts are embolized. 106 109 After TIPS placement, nearly one-third of SPSSs remained unchanged, although with a reduction in portal pressure. He et al proposed prophylactic embolization of SPSS during TIPS, and showed that the risk of HE was similar to those without shunts [hazard ratio (HR) for HE in 5 years of 1 (TIPS) versus 1.38 (1.08–1.77) (TIPS + SPSS) versus 0.82 (0.49–1.37) (TIPS + embolization); p = 0.029].…”
Section: Spss and Outcomes After Tipsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HVPG measurement procedures were described as previous studies [ 14 , 15 ]: in brief, a 7-F balloon-tipped catheter (Edwards Lifesciences, Irvine, California, USA) was guided into the right or middle hepatic vein to measure the WHVP and FHVP, for three times, and the HVPG was calculated. After the initial HVPG measurement, the patients received oral propranolol or carvedilol.…”
Section: Methodsmentioning
confidence: 99%